Resource management system for scientific virtual laboratory applications. (19th December 2014) - Ezugwu, Absalom E.; Buhari, Seyed M.; Junaidu, Sahalu B.
The paper presents a conceptual framework for a resource management system designed for remote virtual laboratory experimentation in both the natural and physical sciences domains. One of the key problems addressed in this paper is the use of a mathematical model to solve resource allocation or task scheduling problems in a dynamic Grid environment that consists of a heterogeneous distributed cyberinfrastructure. The main focus of this paper however includes: architectural design model for scientific virtual laboratory tasks scheduling framework, resource allocation matchmaking algorithm design, mathematical modelling of resource allocation optimisation and computational analysis of the proposed system. The research work is in line with the on–going IT infrastructure networking project at the Ahmadu Bello University, Zaria, Nigeria.